Efecto de las fases lunares en la propagación de caco clonal CCN-51 (Theobroma cacao L.) empleando tres tipos de injertos. - Zambrano Flores, Jeison Daniel (2017)
The present research project was carried out in the ornamental and medicinal plants program of the experimental farm "La María" of the Faculty of Animal Sciences belonging to Quevedo State Technical University (UTEQ) between December 2016 To the March of 2017. With the objective of evaluating the effect of the lunar phases in the propagation of clonal cocoa CCN-51, (Theobroma cacao L.), using three types of grafts. Patterns of 60 days of age will be used. A four-phase bifactorial arrangement (new moon, crescent moon, full moon, waning quarter) by three grafting methods (lateral spike, terminal spike, bud or patch) will be used with four replications. The evaluated were percentage of catch (PP), number of shoots, number of true leaves, length of shoots, percentage of survival (PS), and plants suitable for transplantation. The results were: Grafting methods that presented higher percentages of sting, lateral spike with 95.00% and yolk with 85.00% were found an effect among the Lunar phases since different interactions were found in two variables, the Factor grafting method presented major (P> 0.05) in the shoot length, number of shoots length of shoots, number of true leaves, plants suitable for transplantation, being thus, the growing moon showed significance (P> 0.05) in the length of shoots with 5.38 cm at 60 days. Differences were found in the number of true leaves for the lateral spike method with 10.69 true leaves at 60 days. Differences were found in the number of outbreaks for the lateral spike method with 3.25 shoots. Differences were found in transplant plants for the lateral spike method with 4.37 plants suitable for transplantation at 60 days.